A retrospective analysis of post‐operative outcomes in a series of 108 labial gland biopsies. (24th February 2014) - Ali, S.; Patel, N.; Challacombe, S.
Abstract Aim Histopathological assessment of labial salivary glands has long been a core part of the diagnostic criteria for Sjogren's Syndrome. Biopsy of labial salivary glands is technique sensitive and has post‐operative complications which can affect the patient's quality of life. Varying techniques for labial gland biopsy and associated complications are described in the literature. This article gives a step‐by‐step account of an effective technique for labial gland biopsy as described by Daniels in 1984 and provides a retrospective analysis of the post‐operative complications in a series of 108 labial gland biopsies. Materials and methods A retrospective, post‐operative telephone survey was carried out to study the post‐operative complications of labial gland biopsies performed by a single operator. All consecutive patients (180) who had labial gland biopsies between October 2010 and August 2012 at the Department of Oral Medicine at Guy's Hospital were called, and 108 surveys were successfully completed. The telephone questionnaires aimed to find out medium and long‐term complications of labial gland biopsies to include subjective measures of post‐operative pain, swelling and paraesthesia. Results One patient out of 108 patients (0.9%) reported pain that lasted ≥ 6 months, and six patients (5.5%) reported swelling that lasted > 2 weeks. Three patients (2.8%) reported paraesthesia lasting ≥ 6 months with a median bother score of 0. All biopsies provided sufficient glands to allow for histopathological diagnosis. Conclusions This article describes a safe and effective technique for labial gland biopsy. Despite a low complication rate, informed consent is essential.